Emotions and effectiveness: driving and restraining forces of a group development - Ramalho, Ana Catarina (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
More and more, teams are a strategic fator to achieve organizational success. This way, an effective management of a team will lead to fulfil organizational and team goals. Several authors (e.g. Agazarian & Gantt, 2003; Miguez & Lourenço, 2001) are demonstrating that groups evolve over time and the best way to manage a group is considering its evolutionary basis and working on its driving and restraining forces. The present research aimed to find out more about how emotions and perceived team effectiveness impact the group development, because teams are emotional entities and emotions are associated with several outcomes (as motivation and commitment) as also the perception of work team effectiveness can work on benefit of the group. This is a quantitative study conducted by questionnaire and the sample is composed by 26 teams, comprising 142 employees, from all departments of an industrial company. The results pointed differences among group development phases concerning a) the expression of negative emotions, b) faking and suppressing emotions and c) perception of team effectiveness and, d) it also reinforced, a positive association between positive emotions and perception of team effectiveness. In order to contribute to a better management of teams, this research presents some practical implications to improve a leader’s role in coordinating a team to fulfil grupal and organizational outcomes.